Spectroscopic and luminescence properties of erbium ions in transparent glass-ceramics containing (ER,YB)NBO4 nanocrystals - Skoptsov, N. A.; Dymshits, O. S.; Zhilin, A. A.; Alekseeva, I. P.; Yumashev, K. V. (БНТУ, 2014)
Transparent glass-ceramics containing nanocrystals of (Er,Yb)NbO4 and β-quartz solid solution have been prepared; their absorption spectra, IR and up-conversion luminescence spectra have been studied. Spectral-luminescent characteristics prove these materials to be promising media for 1.5 μm laser generation.